PERFORMANCE TESTING ANALYSIS OF BANDUNGTANGINAS APPLICATION WITH JMETER - Ekky Novriza Alam; Fitriyana Dewi (School of Industrial and System Engineering, Telkom University, 2022)
The bandungtanginas.id application was created to serve the needs of data collection on maternal andchild health at every posyandu in the city of Bandung. This application is planned to be able to servearound 1,982 posyandu in the city of Bandung, around 10,000 users, who are expected to be able toaccess the bandungtanginas.id application. In the current condition of the application supportinfrastructure still has limitations in supporting the bandungtanginas.id application. Withspecifications that tend to be low, an improvement effort is needed through generating applicationusage scenarios so that the services provided can be optimally available using the existinginfrastructure. This research focuses on analyzing the application performance by using load testing.This research has four stages: determining the test's purpose, creating a test scenario, carrying outscenario testing, and analyzing the results. The analysis will be carried out with the results of loadtesting experiments based on the scenarios that have been made. Test scenarios are made to obtainexperimental data, last further analysis and conclusions will be made. Scenarios are created based onan estimate of the optimal number of users the application should serve. The test scenario will use atarget user of between 10 – 200 users who are divided in five groups of load testing scenarios. Fromthis trial, it will be seen how the performance of the bandungtanginas.id application for each scenariogroup that has been created. The result of this study showed that the best scenario forbandungtanginas.id application could serve users in the range of 30-50 users. It is obtained from theresponse time results, which show the average results are under 30 seconds according to the SLA(Service Level Agreement) standard for application users.